Method for preparing high-nickel positive electrode material through ultralow-temperature composite coating, high-nickel positive electrode material and lithium ion battery

By using PVDF+H3BO3 low-temperature coating technology on high nickel positive electrode materials, a uniformly dense protective layer and a high ionic conductivity LBO coating are formed, which solves the layered structure changes caused by excessive deliquification of high nickel positive electrode materials. and side reaction problems, achieving better cycle stability and storage performance.

CN119400812APending Publication Date: 2025-02-07CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST

Patent Information

Application Number
CN202411291551.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The layered structure changes due to excessive deliquification during operation, forming an inert layer and side reactions, resulting in increased polarization of the battery and rapid attenuation of capacity, limiting its practical application.

Method used

PVDF+H3BO3 is used as a low-temperature co-solvent, and the low-temperature melting of PVDF and boric acid is used to promote the diffusion of nano-oxides on the surface of the positive electrode material, forming a uniform and dense protective layer, avoiding non-chemically active cation penetration, and passing through H3BO3 and high nickel Residual alkali reaction on the surface of the material produces a high ionic conductivity LBO coating.

Benefits of technology

It effectively avoids the problem of reduced capacity during high-temperature coating and insufficient cladding density, improves the transmission efficiency of Li+ on the material surface, and enhances the material's cycle stability and storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400812A_ABST
    Figure CN119400812A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-nickel positive electrode material through ultralow-temperature composite coating, the high-nickel positive electrode material and a lithium ion battery. An uncoated high-nickel positive electrode material is obtained through one-time sintering, PVDF / H3BO3 is adopted as a cosolvent, a metal oxide, phosphate and the like are adopted as coating materials, and high-compactness uniform coating of the positive electrode material in an ultralow-temperature environment is achieved. When a traditional high-temperature technology is adopted for coating, due to the fact that materials such as metal oxide and phosphate are inactive, a large number of inactive cations are easily embedded into crystal lattices of the materials due to the high sintering temperature. On one hand, the capacity of the positive electrode material is reduced, and on the other hand, the isolation effect of the coating layer on electrolyte becomes poor due to the reduction of the density of the coating layer. The coating layer prepared by the method is good in uniformity and high in compactness, the discharge capacity, the cycle life, the rate capability and the safety performance of the positive electrode material can be effectively improved, the technological process is simple, the production cost is low, and the method is suitable for industrial production of products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery positive electrode materials, and in particular relates to a method for preparing a high-nickel positive electrode material by ultra-low temperature composite coating, a high-nickel positive electrode material and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of small size, high energy density, long cycle life, low self-discharge rate, and no memory effect, and are widely used in portable electronic devices and electric vehicles. Currently, the commonly used positive electrode materials for lithium-ion batteries include lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, ternary materials and high-nickel materials. Among them, high-nickel positive electrode materials are considered to be one of the most promising positive electrode materials due to their high capacity.

[0003] For high-nickel materials, as the nickel content increases, the specific capacity of the material increases, which can better meet the current electric vehicle's growing demand for battery energy density. When the positive electrode material is working, excessive lithium removal from the electrode surface will cause the layered structure of the high-nickel material to transform into a spinel structure and an inert rock salt structure, and form a thicker inert layer on the surface of the material. In addition, the strong oxidizing Ni on the surface of the positive electrode material 4+ Severe side reactions occur with the electrolyte, causing the battery to produce gas bulges, and also causing the polarization of the battery to increase and the capacity to decay rapidly, which greatly limits the practical application of high-nickel positive electrode materials.

[0004] Surface coating is an effective way to improve the performance of high nickel cathode materials. The most common coating is generally metal oxide coating, such as Al 2 O 3 、ZrO 2 ,MgO,TiO 2 etc. have been widely studied as coating materials. The coating layer can avoid direct contact between the positive electrode material and the electrolyte, inhibit the occurrence of interfacial side reactions, reduce the corrosion of HF in the electrolyte on the positive electrode material, and improve the structural stability and thermal stability of the material. However, metal oxides themselves are electrochemically inactive and require a higher coating temperature. During the high-temperature coating process, chemically inactive cations will be embedded in the material's lattice in large quantities. In addition to causing a decrease in the capacity of the material, the density of the coating layer is also poor, and it cannot effectively isolate the contact between the electrolyte and the positive electrode material.

[0005] For example, CN116666592A discloses a method for preparing a functional polymer-coated high-nickel positive electrode material, which first dissolves polyethylene glycol diamine in N, N-dimethylacetamide, and then adds diisocyanate and flame retardant to prepare a solution. Then, the high-nickel positive electrode material is added, stirred and reacted, and a modified high-nickel positive electrode material with a coating layer is obtained. However, N, N-dimethylacetamide is a toxic, flammable and explosive solvent, which puts forward higher requirements for safe production and environmental protection, and is not conducive to large-scale production. CN116565164A discloses a method for preparing a high-safety modified high-nickel positive electrode material, which dissolves the high-nickel positive electrode material and ethyl cyanoacrylate in acetone respectively, stirs and mixes them evenly under an argon atmosphere, and then stirs and polymerizes them in the air, removes the solvent, and dries to obtain a polyethyl cyanoacrylate-coated high-nickel positive electrode material, which effectively improves the cycle stability and safety of the high-nickel positive electrode material. However, this method uses flammable, toxic and irritating acetone as a solvent, which is not suitable for large-scale industrial production. CN116093332A discloses a high-nickel positive electrode material and a preparation method thereof and a lithium-ion battery, which is coated with a boric acid solution. The high-nickel positive electrode material obtained by mixing the boric acid solution with a positive electrode material matrix and then sintering the obtained material is coated with lithium borate inside and on the surface, thereby improving the discharge capacity of the material and the electrochemical performance of the battery. However, the boric acid solution uses water as a solvent, which is not suitable for coating high-nickel materials with a high Ni content, and a single boric acid coating is insufficient to form a high-strength and high-stability coating layer, and the improvement of the material cycle stability is limited. Summary of the invention

[0006] In view of the current problems, the present invention provides a method for preparing a high-nickel positive electrode material by ultra-low temperature composite coating, a high-nickel positive electrode material and a lithium-ion battery, using PVDF+H 3 BO 3 As a low-temperature cosolvent, PVDF and boric acid are used to promote the diffusion of nano-oxides on the surface of the positive electrode material by means of the low-temperature melting effect, avoiding the shedding of the low-temperature coating layer and forming a uniform and dense protective layer. This method effectively avoids the penetration of non-chemically active cations into the interior of the single crystal during high-temperature coating, thus avoiding the decrease in capacity. In addition, H 3 BO 3 It is a lithium reactive substance that can react with the residual alkali on the surface of high-nickel materials at low temperatures, consume the residual alkali on the surface of high-nickel materials, and generate an LBO coating layer with high ionic conductivity, thereby improving Li +The transmission efficiency on the material surface enables the positive electrode material to exhibit better rate performance. On the one hand, hydrophobic PVDF can decompose and react with the residual alkali on the surface of the high-nickel positive electrode material to generate a stable LiF coating layer. On the other hand, the unreacted PVDF remaining on the material surface can also inhibit the water absorption of the high-nickel material and improve the storage performance of the product. In addition, boric acid, as a glassy coating material, adopts a multi-composite coating method to avoid the problem of insufficient coating stability when a single boric acid coating is used, and effectively improves the cycle stability of the high-nickel material.

[0007] The present invention is achieved by a method for preparing a high-nickel positive electrode material by ultra-low temperature composite coating, comprising the following steps:

[0008] Step 1, crushing and sieving the high-nickel positive electrode material after the primary sintering to obtain the high-nickel positive electrode material process material to be coated;

[0009] Step 2: Mix the high nickel cathode material with the solvent H 3 BO 3 Mixing PVDF and additives uniformly in a certain proportion to obtain a uniformly mixed material to be sintered;

[0010] Step 3, sintering the evenly mixed materials to be sintered at low temperature, and screening and removing iron from the sintered materials to obtain high-nickel positive electrode materials.

[0011] Wherein, the high nickel positive electrode material is nickel cobalt manganese granular oxide or nickel cobalt aluminum granular oxide, and the molecular formula is LiNi x Co y Mn (1-x-y) O 2 or LiNi x Co y Al (1-x-y) O 2 , where x=0.80~0.98, y=0.01~0.2, and 1-xy>0.

[0012] Wherein, in the step 1, based on the high nickel positive electrode material process material, the co-solvent H 3 BO 3 The addition amount is 0.1% to 5.0% by mass, and the addition amount of oily PVDF is 0.1% to 5.0% by mass; the additive is Sb 2 O 3 , 2 O 5 , Nb 2 O 3 , Mo 2 O 3 , WO 3 , ZrO 2 , Al2 O 3 ,MgO,Y 2 O 3 , TiO 2 , CeO 2 ,Co(OH) 2 , Zr(HPO 4 ) 2 , La 2 O 3 One or more of the nanopowders have an element coating amount of 0.05% to 5.0% by mole percentage.

[0013] Wherein, in step 3, the low-temperature sintering temperature is between 150° C. and 500° C., the sintering atmosphere is oxygen, the oxygen concentration is ≥90%, the sintering time is between 2 and 15 hours, and the percentage is volume percentage.

[0014] The high-nickel positive electrode material is prepared by the method for preparing the high-nickel positive electrode material by ultra-low temperature composite coating.

[0015] A lithium-ion battery adopts the high-nickel positive electrode material.

[0016] The advantages and positive effects of the present invention are:

[0017] (1) The present invention selects PVDF+H with a low melting point 3 BO 3 As a co-solvent, PVDF and boric acid can be used to promote the diffusion of nano-oxides on the surface of the positive electrode material by virtue of their low-temperature melting effect, and can form a uniform and dense protective layer on the surface of the material under low-temperature conditions. 3 BO 3 After reacting with the residual alkali on the surface of the high nickel material, an LBO coating layer with high ionic conductivity is generated, which can improve the Li + The transmission efficiency on the material surface. On the one hand, the hydrophobic PVDF can react with the residual alkali on the surface of the high-nickel positive electrode material to generate a stable LiF coating layer. On the other hand, the unreacted PVDF remaining on the surface of the material can also inhibit the water absorption of the high-nickel material and improve the storage performance of the product.

[0018] (2) The product prepared by the present invention has high capacity and good circulation, and the coating is carried out at a relatively low temperature, which effectively reduces the production cost of the product. The process flow is simple and reliable, which is very conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 SEM test images of the high nickel positive electrode material of Example 1 of the present invention and the comparative example. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.

[0021] The method for preparing high-nickel positive electrode material by ultra-low temperature composite coating of the present invention comprises the following steps:

[0022] Step 1, crushing and sieving the high-nickel positive electrode material after the primary sintering to obtain the high-nickel positive electrode material process material to be coated;

[0023] Step 2: Mix the high nickel cathode material with the solvent H 3 BO 3 Mixing PVDF and additives uniformly in a certain proportion to obtain a uniformly mixed material to be sintered;

[0024] Step 3, sintering the evenly mixed materials to be sintered at low temperature, and screening and removing iron from the sintered materials to obtain high-nickel positive electrode materials.

[0025] Wherein, the high nickel positive electrode material is nickel cobalt manganese granular oxide or nickel cobalt aluminum granular oxide, and the molecular formula is LiNi x Co y Mn (1-x-y) O 2 or LiNi x Co y Al (1-x-y) O 2 , where x=0.80~0.98, y=0.01~0.2, and 1-xy>0.

[0026] Wherein, in the step 1, based on the high nickel positive electrode material process material, the co-solvent H 3 BO 3 The addition amount is 0.1% to 5.0% by mass, and the addition amount of oily PVDF is 0.1% to 5.0% by mass; the additive is Sb 2 O 3 , 2 O 5 , Nb 2 O 3 , Mo 2 O 3 , WO 3 , ZrO 2 , Al 2 O 3 ,MgO,Y 2 O 3 , TiO 2 , CeO 2 ,Co(OH) 2 , Zr(HPO4 ) 2 , La 2 O 3 One or more of the nanopowders have an element coating amount of 0.05% to 5.0% by mole percentage.

[0027] Wherein, in step 3, the low-temperature sintering temperature is between 150° C. and 500° C., the sintering atmosphere is oxygen, the oxygen concentration is ≥90%, the sintering time is between 2 and 15 hours, and the percentage is volume percentage.

[0028] The high-nickel positive electrode material is prepared by the method for preparing the high-nickel positive electrode material by ultra-low temperature composite coating.

[0029] A lithium-ion battery adopts the high-nickel positive electrode material.

[0030] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail in conjunction with the embodiments below. The present invention focuses on explaining the influence of the coating process on the positive electrode material. The following embodiments all use the LiNi to be coated 0.92 Co 0.05 Mn 0.03 O 2 The positive electrode material is described below. Take 1000gNi 0.92 Co 0.05 Mn 0.03 (OH) 2 The precursor was mixed with 452.6 g LiOH.H2O, and then sintered in an oxygen atmosphere, first at 450 °C for 5 h, and then at 730 °C for 15 h to obtain a LiNi 0.92 Co 0.05 Mn 0.03 O 2 Positive electrode material. After crushing and screening, the LiNi to be coated is obtained. 0.92 Co 0.05 Mn 0.03 O 2 Positive electrode material. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0031] Example 1

[0032] (1) Weigh 1000g of LiNi to be coated 0.92 Co 0.05 Mn 0.03 O 2 Positive electrode material: weigh 10g of boric acid, 1.084g of Al 2 O 3 , and after uniform mixing, the material to be sintered is obtained.

[0033] (2) The uniformly mixed materials to be sintered are sintered in a sintering furnace, oxygen is passed through, the sintering temperature is 300°C, and the sintering time is 8 hours. After screening and iron removal, the coated high-nickel positive electrode material is obtained.

[0034] Example 2

[0035] (1) Weigh 1000g of LiNi to be coated 0.92 Co 0.05 Mn 0.03 O 2 Positive electrode material: weigh 10g PVDF, 0.541g Al 2 O 3 , and after uniform mixing, the material to be sintered is obtained.

[0036] (2) The uniformly mixed materials to be sintered are sintered in a sintering furnace, oxygen is passed through, the sintering temperature is 250°C, and the sintering time is 8 hours. After screening and iron removal, the coated high-nickel positive electrode material is obtained.

[0037] Example 3

[0038] (1) Weigh 1000g of LiNi to be coated 0.92 Co 0.05 Mn 0.03 O 2 Positive electrode materials: weigh 10g of boric acid, 10g of PVDF, 0.541g of Al 2 O 3 , 1.729 g of La 2 O 3 , 1.307 g ZrO 2 , and after uniform mixing, the material to be sintered is obtained.

[0039] (2) The uniformly mixed materials to be sintered are sintered in a sintering furnace, oxygen is passed through, the sintering temperature is 350°C, and the sintering time is 8 hours. After screening and iron removal, the coated high-nickel positive electrode material is obtained.

[0040] Example 4

[0041] (1) Weigh 1000g of LiNi to be coated 0.92 Co 0.05 Mn 0.03 O 2 Positive electrode materials: weigh 5g of PVDF, 5g of boric acid, 0.541g of Al 2 O 3 , 2.543 g TiO 2 , 3.196 g of Zr(HPO 4 ) 2 , and after uniform mixing, the material to be sintered is obtained.

[0042] (2) The uniformly mixed materials to be sintered are sintered in a sintering furnace, oxygen is passed through, the sintering temperature is 400°C, and the sintering time is 8 hours. After screening and iron removal, the coated high-nickel positive electrode material is obtained.

[0043] Comparative Example 1

[0044] (1) Weigh 1000g of LiNi to be coated 0.92 Co 0.05 Mn 0.03 O 2 Positive electrode material, weigh 1.082g of Al 2 O 3 , and after uniform mixing, the material to be sintered is obtained.

[0045] (2) The uniformly mixed materials to be sintered are sintered in a sintering furnace, oxygen is passed through, the sintering temperature is 300°C, and the sintering time is 8 hours. After screening and iron removal, the coated high-nickel positive electrode material is obtained.

[0046] Comparative Example 2

[0047] (1) Weigh 1000g of LiNi to be coated 0.92 Co 0.05 Mn 0.03 O 2 Positive electrode material, weigh 1.082g of Al 2 O 3 , and after uniform mixing, the material to be sintered is obtained.

[0048] (2) The uniformly mixed materials to be sintered are sintered in a sintering furnace, oxygen is passed through, the sintering temperature is 600°C, and the sintering time is 8 hours. After screening and iron removal, the coated high-nickel positive electrode material is obtained.

[0049] Performance Test 1

[0050] The residual alkali of the high nickel positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 was tested respectively, and the test method was as follows:

[0051] a) Weigh 20.0±0.1g of sample into a 150-250mL dry and clean conical flask and record the mass (m 1 ), add 100mL of distilled water, and record the mass of water added (m 2 ), add magnetic stirring to the conical flask, cover with plastic wrap, and stir for 5 minutes;

[0052] b) After stirring, let the conical flask stand for 1 to 2 minutes, take the supernatant and filter it in a funnel with filter paper. Filter the filtrate into a beaker and take about 30 mL;

[0053] c) Transfer 20.0 mL of the filtrate into a 150-250 mL conical flask and record the mass of the filtrate (m 3 ), add 1 drop of phenolphthalein as an indicator to the filtrate, the solution turns red, and 0.1 mol / L hydrochloric acid is used to titrate the solution to colorless, and the amount of hydrochloric acid used (V 1 ), add 1 drop of methyl orange indicator, the solution is yellow, continue to titrate with 0.1mol / L hydrochloric acid until the solution is orange, that is, the end point is reached, record the amount of hydrochloric acid used (V 2 ).

[0054] Li 2 CO 3 The content is calculated according to formula (A.1):

[0055] Li 2 CO 3 =C(HCl)×2(V 2 -V 1 )×N 1 ×m 2 / m 1 / m 3 / 2 / 1000×100%.......(A.1)

[0056] The content of LiOH is calculated according to formula (A.2):

[0057] LiOH=C(HCl)×(2V 1 -V 2 )×N 2 ×m 2 / m 1 / m 3 / 1000×100%........(A.2)

[0058] Residual alkali Li + The content is calculated according to formula (A.3):

[0059] Li + =Li 2 CO 3 *N 3 *2 / N 1 +LiOH*N 3 / N 2 ...............(A.3)

[0060] Where, C(HCl): concentration of hydrochloric acid standard solution; V 1 : The volume of hydrochloric acid consumed for the first time; V 2 : The volume of hydrochloric acid consumed for the second time; m 1 : The mass of solid powder; m 2: The mass of pure water added; m 3 : The mass of the filtrate after filtration; N 1 :Li 2 CO 3 Molar mass, 73.89 g / mol; N 2 : LiOH molar mass, 23.95 g / mol; N 3 :Li + Molar mass, 6.941 g / mol.

[0061] Table 1 Residual alkali content test results

[0062] Product Number LiOH <![CDATA[Li 2 CO 3 ]]> <![CDATA[Li + ]]> Example 1 0.385% 0.324% 0.172% Example 2 0.332% 0.285% 0.150% Example 3 0.301% 0.215% 0.128% Example 4 0.321% 0.295% 0.148% Comparative Example 1 0.454% 0.385% 0.204% Comparative Example 2 0.462% 0.335% 0.197%

[0063] It can be seen from the data in Table 1 that the residual alkali content of Examples 1 to 4 is relatively low, which indicates that H 3 BO 3 +PVDF coating can effectively reduce the residual alkali on the surface of the material. Comparative Examples 1 and 2 use traditional coating technology, and the residual alkali is relatively high.

[0064] Performance Test 2

[0065] In a dry room environment (ambient humidity ≤ 10%), Supper-P is used as a conductive agent and PVDF solution (6wt%, solvent is NMP) is used as a binder. 5.400g±0.010g of positive electrode material, 0.3000g±0.0010g of Supper-P, 5.000g±0.020g of PVDF solution, add appropriate amount of N-methyl-2-pyrrolidone and stir for 2~4h to make a paste positive electrode mixture slurry. The slurry is evenly coated on aluminum foil, dried at 120℃±3℃ in an oven, and then the pole piece is rolled to the required thickness, and the test electrode of the appropriate size is cut out, and then dried, sliced, assembled into batteries, and the electrical performance tests are carried out respectively. Positive electrode sheets were prepared using the positive electrode materials prepared in Examples 1 to 4 and the positive electrode materials prepared in Comparative Examples 1 to 3, and the test results are shown in Table 2.

[0066] The discharge capacity and cycle performance were tested at 0.2C, and the discharge capacity test conditions were: room temperature 25°C, voltage range 3.0-4.3V. The cycle performance test conditions were: voltage range 3.0-4.3V, 1.0C cycle at 25°C for 60 cycles.

[0067] Table 2 Discharge capacity and cycle performance test data

[0068]

[0069]

[0070] By analyzing the data in Table 2, Example 1 ~ Example 4 showed good cycle stability, indicating that the use of co-solvent for low-temperature coating can effectively improve the cycle stability of the material. Comparative Example 1 had poor cycle stability, indicating that the coating effect was not good. Comparative Example 2 increased the sintering temperature, and the cycle stability was improved, but the excessively high sintering temperature caused the positive electrode material capacity to decrease.

[0071] Performance Test 3

[0072] The SEM of the product was further tested, and Example 1 and Comparative Example 2 were selected for comparison. The test results are as follows: Figure 1 As shown in the figure, it can be seen that the surface of the sample of Example 1 after low-temperature coating has an obvious dense coating layer, which can protect the positive electrode material, while no obvious coating layer is observed on the surface of the sample of Comparative Example 2 after high-temperature coating.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents, and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing high-nickel positive electrode materials by ultra-low temperature composite coating, characterized in that: The following steps are involved: Step 1, crushing and sieving the high-nickel positive electrode material after the primary sintering to obtain the high-nickel positive electrode material process material to be coated; Step 2, mixing the high nickel cathode material process material with the co-solvent H3BO3 and PVDF and the additive in a certain proportion to obtain a uniformly mixed material to be sintered; Step 3, sintering the evenly mixed materials to be sintered at low temperature, and screening and removing iron from the sintered materials to obtain high-nickel positive electrode materials.

2. The method for preparing high-nickel positive electrode material by ultra-low temperature composite coating according to claim 1, characterized in that: In step 1, the high nickel positive electrode material is nickel cobalt manganese granular oxide or nickel cobalt aluminum granular oxide, and the molecular formula is LiNi x Co y Mn (1-x-y) O2 or LiNi x Co y Al (1-x-y) O2, wherein x=0.80~0.98, y=0.01~0.2, and 1-xy>0.

3. The method for preparing high-nickel positive electrode material by ultra-low temperature composite coating according to claim 1 or 2, characterized in that: In the step 1, based on the high nickel positive electrode material process material, the amount of the co-solvent H3BO3 added is 0.1% to 5.0% by mass, and the amount of oily PVDF added is 0.1% to 5.0% by mass; the additive is one or more of Sb2O3, Ta2O5, Nb2O3, Mo2O3, WO3, ZrO2, Al2O3, MgO, Y2O3, TiO2, CeO2, Co(OH)2, Zr(HPO4)2, La2O3 nanopowders, and the element coating amount is 0.05% to 5.0% by molar percentage.

4. The method for preparing high-nickel positive electrode material by ultra-low temperature composite coating according to claim 1, characterized in that: In step 3, the low-temperature sintering temperature is between 150° C. and 500° C., the sintering atmosphere is oxygen, the oxygen concentration is ≥ 90%, the sintering time is between 2 and 15 hours, and the percentage is volume percentage.

5. The high-nickel positive electrode material obtained by the method for preparing high-nickel positive electrode material by ultra-low temperature composite coating as described in any one of claims 1 to 4.

6. A lithium ion battery, characterized in that: The high-nickel positive electrode material according to claim 5 is used.

Citation Information

Patent Citations

  • Preparation method of dual-layer coated high-nickel ternary positive electrode material

    CN110176593A

  • Preparation method of low-cost high-performance high-nickel positive electrode material

    CN116404123A

  • Video Conference Recording Service

    KR1020250072211A

  • Doping and coating method, method for modifying ternary positive electrode material using same, and use

    WO2023005237A1

Cited By

  • Single-crystal layered sodium ion positive electrode material and preparation method thereof

    CN121506935A